New record of begonia inermis (Begoniaceae) to the Argentinian flora and a new synonym of B. fischeri - Zanotti, Christian Alejandro (2020)
Background and aims: The floristic richness of the province of Misiones (Argentina) has been increased in recent years, since new species have been cited and described for the region. The aims of this study were to revalidate and record Begonia inermis Imrsch. (Begoniaceae) for the Argentinian flora and propose a new synonym, B. hassleri C. DC., for B. fischeri Schrank. M&M: The new material collected and the new synonym were compared with the protologues and original materials of each species (except the original material of B. fischeri that could not be located), and additional specimens were also studied. The morphology was examined using optical microscopy. In addition, floras, taxonomic treatments and updated bibliography for the genus were reviewed. Results and conclusions: The description of the new record is presented, a map with its geographical distribution is added, and field photographs and a key to identify the species of Begonia L. that inhabit Misiones are provided. The number of Begonia species cited for the Argentinian Flora was not modified, since B. inermis is revalidate and also we treat B. hassleri as a synonym of B. fischeri. The ring of trichomes at the apex of the petiole of B. inermis differentiates this species from the other species of Begonia that inhabit in Argentina.